Analisis Faktor Penyebab Anak Usia Dini Mengalami Kesulitan dalam Berhitung di TK Siaga Muda Kec Percut Sei Tuan - Friska Fatimah (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2023)
This study aims to analyze the factors that cause early childhood difficulties in counting at Siaga Muda Kindergarten. Difficulties in counting at an early age can have a long-term impact on children’s future mathematical development, to prevent this, this research was conducted. This research uses a descriptive qualitative method, which is a qualitative approach with observation methods and also interviews with young children and teachers of TK Siaga Muda. The results of this study found several main factors that contribute to numeracy difficulties in early childhood at Siaga Muda Kindergarten. The first is the lack of understanding of basic math concepts such as addition, subtraction and number concepts in children. The second factor is ineffective teaching methods, and the third factor is the lack of time spent practicing. This study recommends several steps to overcome early childhood numeracy difficulties at Siaga Muda Kindergarten. Such as using interactive and interesting teaching approaches, using diverse and creative methods, and the need for close cooperation between teachers, parents and educational institutions. By identifying the factors that cause numeracy difficulties at Siaga Muda Kindergarten, this research is expected to provide valuable input.